PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 49 TAMERAN KECAMATAN BENGKALIS - Norliza, Norliza; Lazim N, Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this Research is the weakness of student,s learning result of subject.It show from 24 student,s 14 students (58,33%) have lower score, and it is only 10 student,s ( 41,66%) have average score 63.23. the KKM of this school is 70. According to that problem, the Research by implementing cooperative learning model Talking Stick . in cycle I,the percentage of teachers activity in First meeting is adquate 58,33 % .In second meeting ,teachers activity significantly increased to 75,00% with good category. In cycle II, first meeting was in good category 79,16% and second meeting indicated a very good category 91,66% Meanwhile, the activity of student,s also improved. In cycle I indicated 54,16% in adequate category and in cycle II has increased up to 70,83% with good category. In cycle II, First meeting, the activity of students has been increasing to 75,00% with good category and second meeting indicated very good category 87,50% . An average score of student,s learning result before implementation is 63,23. It increased to 68,54 in cycle I,and 72,08 in cycle II. In classical completeness, cycle I and cycle II Wet achieved. In conclussion, implementation cooperative learning model Talking Stick can improve student,s learning result of fourth grade students of SDN 49 Tameran Kecamatan Bengkalis in social subject.Key words: Cooperative modelTalking Stick,learning result of social subject